Case report: The gastrointestinal nematode Strongylus vulgaris as a cause of hoof abscess in a donkey - Lina Stahel; Naomi Ana Bigler; Felix Grimm; Manuela Schnyder; Andreas W. Oehm (BMC Veterinary Research)
Abstract Background Gastrointestinal helminths of the Strongylus genus can be very pathogenic in equids mainly because of migratory larval and subadult stages invading arteries of the mesenterium. However, the extraintestinal, aberrant presence of these stages has been observed. Case presentation A 19-year-old male donkey presented with severe lameness in the right front limb. After unsuccessful hoof wraps, diagnostic imaging was performed. Removal of the sole horn led to the discovery of a sizeable abscess containing a single nematode. The helminth was removed and parasitologically examined. The abscess was treated with surgical drainage, wound care, and medicinal fly larvae. Anthelmintic treatment with oral ivermectin (200 µg/kg body weight) was initiated. Parasitological follow-up examinations were conducted two weeks afterwards and at seven and ten months after initial diagnosis. The nematode was identified as adult female specimen of Strongylus vulgaris. Coproscopic examination of the animal and four herd mates confirmed the presence of S. vulgaris in the group. The hoof abscess healed within two months and lameness completely resolved. All parasitological follow-up examination demonstrated anthelmintic efficacy and absence of S. vulgaris, indicating sustained parasite control. Conclusions This case represents the first report of ectopic occurrence of S. vulgaris causing a hoof abscess inducing lameness in a donkey. The healing of the abscess was without complications as soon as the source of the condition was removed.